Overexpression of Glycolate Oxidase Confers Improved Photosynthesis under High Light and High Temperature in Rice - Cui, Li-Li; Lu, Yu-sheng; Li, Yong; Yang, Chengwei; Peng, Xin-Xiang (Frontiers in Plant Science, 2016)
While glycolate oxidase (GLO) is well known as a key enzyme for the photorespiratory metabolism in plants, its physiological function and mechanism remains to be further clarified. Our previous studies have shown that suppression of GLO in rice leads to stunted growth and inhibited photosynthesis (Pn) which is positively and linearly correlated with decreased GLO activities. It is, therefore, of interest to further understand whether photosynthesis can be improved when GLO is up-regulated? In this study, four independent overexpression rice lines, with gradient increases in GLO activity, were generated and functionally analyzed. Phenotypic observations showed that the growth could be improved when GLO activities were increased by 60% or 100%, whereas reduced growth was noticed when the activity was further increased by 150% or 210%. As compared with WT plants, all the overexpression plants exhibited significantly improved photosynthesis under conditions of high light and high temperature, but not under normal conditions. In addition, the overexpression plants were more resistant to the MV-induced photooxidative stress. It was further demonstrated that the antioxidant enzymes, and the antioxidant metabolite glutathione was not significantly altered in the overexpression plants. In contrast, H2O2 and salicylic acid (SA) were correspondingly induced upon the GLO overexpression. Taken together, the results suggest that GLO may play an important role for plants to cope with high light and high temperature, and that H2O2 and SA may serve as signaling molecules to trigger stress defense responses but antioxidant reactions appear not to be involved in the defense.